2021
DOI: 10.9734/ajaar/2021/v15i130144
|View full text |Cite
|
Sign up to set email alerts
|

Field Performance of Three-way Cross Yellow and White Maize Hybrids in Nepal

Abstract: Maize hybrids can increase production, bridge the yield gap, and boost up domestic production in Nepal. Three-way cross hybrid introduces an alternative to produce low cost hybrid seed for resource poor farmers. A study was performed to identify promising yellow and white maize hybrids developed by International Centre for Maize and Wheat Improvement (CIMMYT), Mexico in Rampur, Nepal. Nineteen three-way cross white maize hybrids with two checks and seventeen yellow maize hybrids with one check were tested in f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 11 publications
2
4
0
Order By: Relevance
“…e differences in the plant height, though being nonsignificant, might be because of the fact that the hybrids were from diversified parent lines [7] and checks were also used in the study, which were of high importance in the study area. Similar to our finding, Tripathi et al [37] and Koirala et al [15] reported that plant height was not significantly different in three-way cross yellow maize hybrids and single-cross hybrids, respectively.…”
Section: Growth Traitssupporting
confidence: 92%
See 1 more Smart Citation
“…e differences in the plant height, though being nonsignificant, might be because of the fact that the hybrids were from diversified parent lines [7] and checks were also used in the study, which were of high importance in the study area. Similar to our finding, Tripathi et al [37] and Koirala et al [15] reported that plant height was not significantly different in three-way cross yellow maize hybrids and single-cross hybrids, respectively.…”
Section: Growth Traitssupporting
confidence: 92%
“…e synthesis silking interval was moderately heritable [35]. High heritability in grain yield and plant height has been reported by Neupane et al [35,36] which contradicted our findings, which are moderately and low heritable traits respectively, but was in line with the findings of Tripathi et al [37]. e expression of a trait is highly influenced by environmental effects and effects on the degree of expression but not on the degree of inheritance [41].…”
Section: Estimation Of Genetic Parametersupporting
confidence: 70%
“…In Nepal, current maize production is 2.71 million tons from a 0.96 million hectare area with an average productivity of 2.84 t ha −1 [2]. Besides being a staple crop of the mid-hill region, maize is the chief ingredient of livestock feeds, especially for rapidly growing poultry [3,4]. Despite the cultivation of several new maize hybrids and improved varieties, national production fails to fulfill total demand, and the country imports maize in large quantities every year [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Anthesis silking interval between 2-4 days are found to have a positive effect on grain yield of maize i.e. ASI is negatively correlated to yield and a close gap in ASI has been reported in maize hybrid by several researchers [ 23 , 37 , 38 , 39 , 40 , 41 ]. The yield and its components showed dependence on the ASI [ 42 ].…”
Section: Resultsmentioning
confidence: 82%